Optimizing Oxygen Transport Through La0.6Sr0.4Co0.2Fe0.8O3-δ Hollow Fiber by Microstructure Modification and Ag/Pt Catalyst Deposition - Han, D.; Sunarso, J.; Tan, X.; Yan, Z.; Liu, Lihong; Liu, Shaomin (American Chemical Society, 2012)
This work compares the oxygen permeation fluxes of five different La0.6Sr0.4Co0.2Fe0.8O3−δ membranes (e.g. disk, conventional hollow fiber, modified hollow fiber, Ag- or Pt-deposited hollow fiber membranes) to elucidate the dominance of a particular oxygen transport limiting step (e.g., bulk-diffusion or surface reaction) within each of these membranes. At 900 °C and 100 mL min–1 helium gas sweep rate, the oxygen fluxes for disk, conventional hollow fiber, modified hollow fiber, Ag-deposited modified hollow fiber, and Pt-deposited modified hollow fiber membranes are 0.10, 0.33, 0.84, 1.42, and 2.62 mL min–1 cm–2, respectively, denoting enhanced performance in this sequential order. More than 300% enhancement of fluxes is evidenced by modifying the geometry from disk to conventional hollow fiber. This is attributed to the thickness reduction from ∼1 mm to ∼0.3 mm, thus implying bulk-diffusion and surface reaction as the jointly limiting transport step for this disk membrane.In contrast to a conventional hollow fiber that has a sandwich cross-sectional structure (e.g. dense center layer sandwiched by two finger-like layers) as well as dense outer and inner circumference surfaces, the modified hollow fiber has only one dense layer in its outer circumference surface with finger-like porous layer extending all the way from outer cross-sectional part to the inner cross-sectional part. This microstructural difference, in turn, provides substantial reduction of membrane thickness and enlarges surface reaction area for modified hollow fiber (relative to conventional hollow fiber), both of which contributes to the reduced bulk-diffusion and surface reaction resistance; evidenced by almost 250% oxygen flux enhancement. To enhance the performance even further, catalyst (e.g., Ag or Pt) deposition on the outer circumference surface of modified hollow fiber can be utilized to reduce its dominating surface reaction resistance. While both catalysts increase the oxygen fluxes, Pt reveals itself as the better candidate relative to Ag due to melting-induced aggregation and growth of Ag at ∼950 °C.